The Effect of Rotation Speed and Time of Milling on Synthesisand Properties of Fluoridated Hydroxyapatite Biomaterial: Synthesis of fluorhydroxyapatite nanopowder - Mohammad Hossein Fathi; Ehsan Mohammad Zahrani (Iranian Journal of Pharmaceutical Sciences, 2008)
Synthetic hydroxyapatite (HA) is the most helpful because of its similarity to natural bone in both crystalline structure and chemical composition. Recently,fluoridated hydroxyapatite (FHA) has been developed in dental and orthopedic application because it has lower solubility than pure HA, while maintaining the comparable bioactivity and biocompatibility. The aim of this study was to synthesis and characterizes FHAnanopowder via mechanochemical activation method. Also the effect of milling time and rotation speed on its properties was investigated.Calcium hydroxide, phosphorous oxide and calcium fluoride powder were used for synthesis of FHA. The math ratio of balls to reactant was 30. Mechanochemical reaction was performed in the planetary ball mill at two rotating speed 300 and 250rpm. Zirconia ball and zirconia vial were used to perform the mechanochemicalprocess. X-ray Diffraction, FTIR spectroscopy and Scanning Electron Microscopy were utilized to characterize FHAnanopowder. The results showed that the synthesis of FHAafter 6 h ball milling at 300 rpm or 10 h milling at 250 rpm was complet.